2021
DOI: 10.1093/rb/rbab037
|View full text |Cite
|
Sign up to set email alerts
|

A sandwich structure composite wound dressing with firmly anchored silver nanoparticles for severe burn wound healing in a porcine model

Abstract: Wounds may remain open for a few weeks in severe burns, which provide an entry point for pathogens and microorganisms invading. Thus, wound dressings with long-term antimicrobial activity are crucial for severe burn wound healing. Here, a sandwich structure composite wound dressing anchored with silver nanoparticles (AgNPs) was developed for severe burn wound healing. AgNPs were in situ synthesized on the fibers of chitosan nonwoven fabric (CSNWF) as the interlayer of wound dressing for sustained release of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 56 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Once in contact with wound exudate, the hydrocolloid particle (CMC sodium carboxymethylcellulose) in the dressing swells after absorbing the exudate, forms a soft, cohesive hydrogel that allows it to absorb the wound exudate while locking it in within the gel, avoiding the risk of exudate leakage as well as the wound skin. Intrasite gel also creates a moist environment conducive to wound healing [20][21][22]. e results of this study showed that after treatment, the positive rate of wound bacterial culture in the observation group was significantly lower than that in the control group.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Once in contact with wound exudate, the hydrocolloid particle (CMC sodium carboxymethylcellulose) in the dressing swells after absorbing the exudate, forms a soft, cohesive hydrogel that allows it to absorb the wound exudate while locking it in within the gel, avoiding the risk of exudate leakage as well as the wound skin. Intrasite gel also creates a moist environment conducive to wound healing [20][21][22]. e results of this study showed that after treatment, the positive rate of wound bacterial culture in the observation group was significantly lower than that in the control group.…”
Section: Discussionmentioning
confidence: 66%
“…Once in contact with wound exudate, the hydrocolloid particle (CMC sodium carboxymethylcellulose) in the dressing swells after absorbing the exudate, forms a soft, cohesive hydrogel that allows it to absorb the wound exudate while locking it in place within the gel, avoiding the risk of exudate leakage as well as macerating the wound skin. Intrasite gel also creates a moist environment conducive to wound healing [ 20 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wound infections are a major challenge in burn care, and severe bacterial infections can result in bacteremia, endocarditis, and high mortality. Currently, antibiotics are widely used to treat bacterial infections; however, the misuse can result in higher bacterial resistance and cross-resistance to clinically important antibiotics. , There is an urgent need to explore new and effective strategies for reducing bacterial drug resistance and preventing bacterial infections. Inspired by the lotus leaf effect, the construction of superhydrophobic surfaces with hierarchical micronanostructures is considered an effective option for preventing bacterial infections.…”
Section: Resultsmentioning
confidence: 99%
“…Functional exploration of polyurethane dressings has primarily used rat, mouse, and rabbit models, with wound repair models from pigs being rarely used [116]. The main disadvantages of using rabbit or rodent models are the differences in skin physiology, healing patterns, and skin-attached hairs.…”
Section: Healing Evaluationsmentioning
confidence: 99%